Security Evaluation Methodology for Teaching and Learning Ecosystem - Pouta, Roope (My University, 2023)
In this thesis my research has focused on security evaluations and audits. How is a good security evaluation method made and what it includes. The purpose of this research is to create a suitable security evaluation methodology for learning ecosystems and test it in a case-study. In the first two chapters I researched general information about already existing security evaluation methods and studies about security in learning platforms in general. What exactly are security evaluations and how those are used. In those chapters I also researched how to build a security evaluation method and then built one for the purpose of this thesis. The last three chapters include the evaluation of the method and a case-study. Where the security evaluation method was tested. All of the requirements that are in the security evaluation method are inspected and also perfected in these chapters. Digital learning platforms are becoming more and more popular. Because of the increasing user amount in said platforms security must be in a good order to protect its users. In my research I prove that security evaluations are necessary for learning ecosystems. There are no drawbacks to the organisation, they can only benefit from it. The case-study was conducted in Turku Research Institute for Learning Analytics (TRILA), where this method was found successful.
Keywords: Security Evaluation, Audit, Learning Ecosystem, Security Training